Design and Performance Analysis of a Flat Plate Collector - Pramanik, Alokesh; Islam, K.; Khan, A.; Hyder, N.; Huq, A. (the Institution of Engineers, Bangladesh, 1999)
In the present work solar thermo-syphon water heating system was designed and performance was tested with single glazing and without glazing. The solar radiation in Dhaka (Latitude 20.34 and 26.38 degree north) in May is 4778 Kwh/m^2 and June is 5416 kwh/m. To keep the cast as minimum as possible the materials are chosen carefully. After fabrication, collector water outlet temperatures, tank outlet temperature, collector plate temperatures, sky condition etc. were recorded to study the performance of the system. On a typical day in the 8th September at 2.15 p.m. the setup achieved an increase in water temperature of 20 degree C within 4 hrs. starting from 10.45 am for solar insulation of 800 W/m^2 with single glazing and in 3rd April at 1.40 pm the setup achieved an increase in water temperature of 15 degree C within 4 hours starting from 8.30 am for solar insulation of 900 w/m^2 without glazing. The performance show that the collector with glazing type may be installed in rural and urban areas where hot water of moderate high temperature is required for day to day use